More Proximal, More Willing to Purchase: The Mechanism for Variability in Consumers’ Purchase Intention Toward Sincere vs. Exciting Brands - Hu, Tingyun; Shi, Bing (Frontiers in Psychology, 2020)
Sincerity and excitement are core brand personality dimensions, which capture the majority of consumers’ personality perceptions associated with brands. Previous research has demonstrated that consumers are more willing to purchase sincere brands than exciting brands. The present research addresses the mechanism underlying this variability. A total of four studies were conducted. Study 1 adopted survey-based design and manipulated brand personality by two versions of fictitious coffee brands. Results showed that sincere (versus exciting) brands elicited more proximal psychological distance and in turn led to higher purchase intention. With a similar procedure, a different sample, and a different product (vacuum cup), Study 2 replicated the pattern demonstrated in Study 1. Moreover, the impact of brand personality upon psychological distance was found to be more prominent among consumers with high (versus low) levels of attachment anxiety. Because psychological distance is proposed and proved to be a critical variable for mediating the variability in purchase intention, we adopted cognitive computerized tasks in Studies 3-4 to test whether stimuli perceived as sincere and exciting will induce different responses relevant to the perceptions of psychological distance. Study 3 adopted a picture-word version of Stroop task to test whether the automatic activation of personality-priming words would carry various perceptions of psychological distance, and results showed that participants classified distance faster when a close (versus far) spatial distance matched sincere words and when a far (versus close) spatial distance matched exciting words. Study 4 adopted the interference task to examine whether visual attention would be affected by personality-priming images, and results indicated a stronger cueing effect and an articulated interference effect for sincere (versus exciting) figures. This research advances the literature of brand personality by probing the important role of psychological distance, and further elaborating on the variability of consumer behavior toward sincere and exciting brands.